Key Technologies of Intelligent Identification of Biomarkers:Review of Research on Association Prediction Between Circular RNA and Disease - Hu, Xuegang; Li, Yang; Wang, Lei; Li, Peipei; You, Zhuhong (Ji suan ji ke xue, 2023)
Biomarker recognition is a major basis for achieving precision medicine, which plays an important role in diagnosing complex diseases, judging disease stages and evaluating the safety and effectiveness of new drugs or therapies in the target population.As the key technology of intelligent identification of biomarkers, the prediction of the association between circular RNA and disease is the key to deeply evaluate and measure the biological process, pathological process and intervention pathological response of subjects, and is one of the effective means and approaches to practice "precision medicine".This paper comprehensively combs and prospects the circular RNA disease association prediction model in biological big data.Specifically, it first discusses the relationship between circRNA and disease in terms of the research background, physicochemical properties and functions of circ-RNAs.Then, it investigates the public database resources of circRNAs and diseases, and summarizes four computational methods of